PENGARUH KOMPETENSI TERHADAP KINERJA APARATUR PENGAWAS INTERN PEMERINTAH (STUDI PADA KANTOR INSPEKTORAT PROVINSI KALIMANTAN UTARA) - Budi Mulyadi; Kartini Maharani Abdul; Erlina Kurnia Asih (Sekolah Tinggi Pariwisata Mataram, 2022)
Government Internal Supevisory Apparatus or as knowing as APIP is an instrument that built with the task of doing an internal control in Central Government and Regional Government, consisting of financial and development supervisory agency (BPKP), Inspectorate General of Ministry, Inspectorate of Province/District/City and Supervisory Internal Unit in another government legal entities according to the civil regulation. his research is to find out the effect of competency on government internal supervisory apparatus at Inspectorate Province of North Borneo. This research is a quantitative research. This research method is used to test the hypotic and find out the effect between variables that has built to be a research model that is to find out the correlation between the Independent variable that is Competency of Independent variable that is performance of APIP. Data Analysis technique that used in testing hypothesis are Ordinary linear regression analysis and structural Equation Modeling (SEM) . That ruquired to do some assumption tests like normalist assumption test , assumption of no outlier, and linearity. This research shows that competency variable gives 80% postive and significant effect to performance of Government Internal Supervisory Apparatus (APIP), and the rest 20% is affected by another factor of this research. Variable competency is seen more 0,82 or 67% on motive indicator while on the performance variable is seen 0,75 or 57% on timeliness indicator.